Fundamental of Entrepreneurship ENT300: Pineapple Farm / Najid Najmudin Abdul Rahim ... [et al.] - Abdul Rahim, Najid Najmudin; Mhd Taha, Muhammad Ariff; Mohd Salim, Mohd Farhan (2009)
Our company name is Pineapple Farm. We use partnership form for our business where there is consisting of four partners. Each partner share and contributes same amount of capital as agreed in our agreement. The business will be place at Samarahan and it will commence beginning 2°° May 2009. All partners are participate in the business management. We all agreed that our company is lead by Najid Najmudin Bin Abdul Rahim as a General Manager and also Administration Manager, while Muhammad Ariff Bin Mhd Taha as Marketing Manager, Mohd Farhan Bin Mohd Salim as Operation Manager and Abdul Qudus Bin Ahmad as Financial Manager. The management is lead by the General Manager. The General Manager is responsible in controlling, leading, organizing and planning the entire business. The Marketing Manager is responsible to preparing the marketing plan which is includes identifying the target market, determining the market size, identifying the competitors, determining the market share, developing sales forecast and marketing strategies. The Operation Manager is to controlled and monitored the operation of our business. Supervisor and 5 workers will be under the supervision of the Operation Manager. This is where quality control and productivity will take place. All jobs relating to office matter is control by Administration Manager. Finally is Financial Manager where it will handle financial matters such as preparing budgets and financial statements for the expenses of each department.